Cultura de inovação em pequenas e médias empresas industriais inovadoras - Sabaini, Wellinton Tesch (2013)
In the last decade, innovation has been regarded as one of the main strategies of enterprises to obtain competitive advantage, becoming a strategic issue in management. Thus, the term culture of innovation has long been employed in academic and business circles, especially in the sense of being a means propitiate of innovation development. However, a literature search showed that culture of innovation is a complex and recent topic that needs more research, and also identified that there is no specific studies on Brazilian companies small and medium sized businesses. Thus, this research aims to identify the cultural manifestations of industrial innovative small and medium size, it is possible to infer a culture of innovation, which provides product innovation in such firms. We conducted a survey of organizational culture by identifying cultural events proposed by Martin (2002): "cultural forms", "formal practices", "informal practices" and "content themes". These manifestations inferred from innovation culture. Therefore, we carried out a qualitative research, and study method multicase applied in three considered innovative companies that develop and manufacture innovative products, winners of FINEP Innovation Award. We used multiple sources of inferences for data collection: semi-structured interviews, non-participant observation and document analysis. 25 interviews were conducted. The analysis was performed according to the categorization process proposed by Flores (1994), opting for a open categorization, so that the analyzed data revealed manifestations more freely as possible. The results showed that the elements of common culture of innovation and the three companies surveyed that are providing innovation were, especially a "formal and informal learning", formal practices of human resources training and education and "selection and hiring , followed by "employee participation" and "market orientation". Although it is common for the three companies, the survey identified that each company has come a different way to build such elements, i.e. each company has its "ingredient" specific to innovate. Furthermore, research has shown that the performance of the founding leaders was one of the factors that contributed to the development of a culture of innovation.